2021
DOI: 10.3390/foods10081861
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Integrated Technology Apps for Supporting Healthy Food Purchasing and Consumption: A Systematic Review

Abstract: A healthy diet is essential for good health and nutrition, though literature showed that there are various factors affecting the intention to purchase and consume healthy food. Technology integration is known to be useful in various aspects, but findings from studies on the efficacy of technology integration to improve healthy food consumption and purchase have largely been inconsistent. Therefore, we aimed to examine the efficacy of interventions that use technology apps to improve healthy food purchasing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 74 publications
(131 reference statements)
1
14
0
9
Order By: Relevance
“…Only a small number of English-language digital health apps have reported their usability evaluation results [ 6 ]. Although the usefulness of technologies has been demonstrated, results on the effectiveness of technology integration on the adoption of healthy eating habits are conflicting [ 15 ]. In 2018, French was spoken in 29 countries on all continents, by approximately 300 million people; 235 million people use it daily, and 90 million people are native speakers [ 16 ]; however, no overall evaluation of French-language nutrition apps has been identified in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Only a small number of English-language digital health apps have reported their usability evaluation results [ 6 ]. Although the usefulness of technologies has been demonstrated, results on the effectiveness of technology integration on the adoption of healthy eating habits are conflicting [ 15 ]. In 2018, French was spoken in 29 countries on all continents, by approximately 300 million people; 235 million people use it daily, and 90 million people are native speakers [ 16 ]; however, no overall evaluation of French-language nutrition apps has been identified in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, prior research in adults has confirmed that engagement with a mHealth technology was a significant predictor of dietary intake behavior change ( 82 ). It will be critically important to identify components of the mHealth intervention, such as increased interactivity, personalization, or individual feedback, which keep children and families engaged with the technology long-term ( 83 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, video-conferencing services had a ten times increase in use, and delivery services had a 30% increase [ 8 ]. However, older adults are not in the age group that could reap the maximum benefits from Internet use as they are deemed not technology savvy and lack digital literacy [ 9 , 10 ]. The Internet, together with electronic gadgets, could be the solution to continue social interaction and support for older people during the pandemic.…”
Section: Introductionmentioning
confidence: 99%